The Development of Village Potential Through Capacity Building in Tunjungtirto Village Singosari Sub-District Malang District - Ruslan, Aulia Tia; Gani, Abdul Juli Andi; Rozikin, Muhammad (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2020)
This study analyze about development of village potential through capacity buildingin Tunjungtirto village, Singosari Sub-District, Malang district. The author analyze that development of village potential through capacity building has five main elements, knowledge in the form of developing educational potential, religious potential, agriculture potential, farm potential and village library. Than leadership by the village head, cooperation between villages, community in the form of village business entity (BUMDesa), travel conscious group and agriculture group. Than online information program which is conducted by village head to facilitate submitting information about village activities to villagers or submitting community suggestions and critisms by online. Leadership by the village head in accordance with the law number 6 of 2014 about village has regulate local village authority. Collaboration between Tunjungtirto village with Lang Lang village about the use of clean water sources. Travel conscious group (Pokdarwis) has develop creativity through mural village and dolanan village to attract tourist.